Axiomatic approach to the multicriteria structural optimization - Pochtman, Yuriy M.; Skalozub, Vladislav V.; Nagornyy, Dmytro V. (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents the axiomatic approach [or solving the multicriteria optimization of thin-walled structure such as vertical cylindrical reservoirs subject to pitting corrosion. The probabilities of derivation of the compromise optimal project based on MaxMin principle are investigated. The analytic dependencies for estimation of the partial criteria weighting coefficients are obtained. The project consists of the optimal thickness of reservoir shell along its height.